TI_GERICHTE 52.2012.494 vom 7. August 2015 , Licenza edilizia in sanatoria per un impianto di climatizzazione con sei unità esterne - TI Tribunale d'appello (2015)
Licenza edilizia in sanatoria per un impianto di climatizzazione con sei unità esterne